Implementation of project-based learning at a technical university: teacher enthusiasm or resistance - Ekaterina A. Gradaleva; Maria Houston (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article describes implementation of project-based learning within the scope of different academic disciplines at a technical university. The research aims at analyzing various problem points that teachers face while organizing project work of students. The reasons complicating proliferation of project-based learning are observed. Methodology includes analysis of pedagogical studies, examination of project-based activities at universities, interviewing, and questionnaire survey. The findings lead to the conclusion that project-based learning is interesting for the majority of educators and is considered to be an effective type of activity. However, it is not widely used at a technical university. This happens because of a number o f difficulties that occur in the process of project planning and implementation. These are the issues of keeping up motivation, the lack of time for doing projects and presenting results, unwillingness of students to take up self-studies, problems with control and assessment, unevenly distributed learning. The author proves the necessity of teacher professional development in this sphere. The most important units of the programme have been specified. It is recommended that the course trains educators to plan projects with due regard to curriculum, to share knowledge and develop skills significant in a specific area of studies, to nurture contemporary co mpetencies, such as confidence, perseverance, innovative thinking, creativity, flexibility, openness, sociability, teamwork. Moreover, the article describes the importance of discussing the methods of implementing short-term and international projects. According to the research, these types of project work are organized less frequently than the other ones.